Melancholy and capitalism - Gimbo, Leda Mendes; Gimbo, Fernando (Passagens: Revista do Programa de Pós-Graduação em Comunicação da Universidade Federal do Ceará, 2025)
This article reconsiders melancholy beyond clinical framing, advancing it as a historical-political affect specific to late capitalism. We trace how nosographic translations flatten singular experiences into “depression” and show how contemporary regimes of life and death—marked by disposability and spectacularized violence—shape collective sensibility. Within this landscape, melancholy operates as an index of forbidden mourning and as a transitional affect: rather than paralysis, it can turn loss into shared memory and memory into common action. We argue for a politics of mourning that de-pathologizes structural pain and works through it as a basis for care, solidarity, and insurgent joy—not compulsory positivity, but the energy of resistance arising from acknowledged vulnerability and social trauma.